The Influence of Parental Support on Learning Motivation: Survey Study at SMKN 65 Jakarta - Kamala , Erdila Imelia; Ulfah, Maria; Kunaeniih (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This research aims to determine the effect of parental support on students' learning motivation at SMKN 65 Jakarta. Parental support plays an important role in a child's educational process, especially in forming high learning motivation. The method used in this research was a survey, this research is quantitative. Involving a number of students from SMKN 65 Jakarta as respondents. Data was collected through a questionnaire designed to measure the level of parental support and student learning motivation. The research results show that there is a positive and significant relationship between parental support and student learning motivation. The higher the support provided by parents, the higher the student's learning motivation. These findings emphasize the important role of parents in supporting their children's educational process to achieve optimal learning outcomes. It is hoped that this research can be a reference for schools and parents in developing strategies to increase student learning motivation.